La deculturación de identidad en El entierro de Cortijo de Edgardo Rodríguez Juliá. - Badillo, William (CIICLA, Universidad de Costa Rica, 2012)
This paper presents the life of a social group that for more than four hundred years has been the victim of cultural isolation. Manufacturing in full swing in mid-twentieth century on the island, the black race did not have the same employment opportunities in urban areas of the city. The author uses the Chronicle Narrative Style to give voice to a helpless social class on their way to a funeral. This article reflects the cultural inequality and segregation along with the negative effects that affect a community.